2014
DOI: 10.1155/2014/273219
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Rhinitis Sicca Anterior with Ectoine Containing Nasal Spray

Abstract: Objectives. The safety and efficacy of ectoine nasal spray and ectoine nasal spray with dexpanthenol in the treatment of rhinitis sicca were evaluated in two studies. Design and Methods. Two noninterventional observational studies were performed to evaluate the efficacy and safety of a nasal spray containing ectoine (study 1) and ectoine/dexpanthenol (study 2) over a period of two weeks including comparable numbers of patients suffering from rhinitis sicca anterior. Patients and physicians were asked to rate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 21 publications
0
21
0
4
Order By: Relevance
“…After 2-3 years of work in harmful production, workers begin to observe the appearance of the first typical symptoms of atrophic rhinitis. Atrophic changes of the nasal mucosa are rarely isolated and are usually with atrophic pharyngitis and laryngitis [15][16][17].…”
Section: Methodsmentioning
confidence: 99%
“…After 2-3 years of work in harmful production, workers begin to observe the appearance of the first typical symptoms of atrophic rhinitis. Atrophic changes of the nasal mucosa are rarely isolated and are usually with atrophic pharyngitis and laryngitis [15][16][17].…”
Section: Methodsmentioning
confidence: 99%
“…Some studies showed that products containing ectoine may be a better alternative to other products, as they reduce ocular and nasal symptoms with no side effects (40)(41)(42). Promising effects such as reduction of nasal airway obstruction and crust formation were also observed in patients with rhinitis sicca anterior treated with nasal spray containing ectoine alone or in combination with dexpanthenol (43).…”
Section: Alleviation Of Inflammatory Reactionmentioning
confidence: 99%
“…Ektoina (kwas 1,4,5,6-tetrahydro-2-metylo-4-pyrimidynokarboksylowy) to cząsteczka naturalnie produkowana przez ekstromofile, bakterie żyjące w trudnych warunkach środowiska. Tworzy ona naturalną barierę ochronną przed oddziaływaniem czynników szkodliwych, takich jak wysoka temperatura, promieniowanie ultrafioletowe czy nadmierna suchość [8,9]. Ekstromofile nabywają odporność poprzez zmianę składu lipidów w błonach komórkowy i regulację wewnątrzkomórkowego stężenia substancji rozpuszczonych o niskiej masie cząsteczkowej, takich jak kompatybilny rozpuszczony roztwór ektoiny.…”
Section: Ektoinaunclassified
“…Ekstromofile nabywają odporność poprzez zmianę składu lipidów w błonach komórkowy i regulację wewnątrzkomórkowego stężenia substancji rozpuszczonych o niskiej masie cząsteczkowej, takich jak kompatybilny rozpuszczony roztwór ektoiny. W badaniach wykazano, że ektoina zapewnia ochronę komórek nabłonkowych, stabilizuje błony komórkowe, nawilża powierzchnię oraz zmniejsza stan zapalny [8][9][10][11][12][13].…”
Section: Ektoinaunclassified
See 1 more Smart Citation